A survey of power-consumption monitoring systems - Adebisi, John A.; Ndjuluwa, Leokadia N.P. (e-Prime, 2024)
•Trends of energy monitoring and consumption – review of past related work•Future trends of remote energy monitoring and control•Reflecting an environmental/economic model for optimal energy monitoring systems by consumers.•Considering energy monitoring from various sources by different organisation to checkmate energy service providers•Presenting different perspectives to remote energy monitoring systems for cost optimization and energy consumption efficiency•Providing superior information and approaches for energy consumption monitoring and Management. Monitoring energy consumption remotely is a problem known to most energy consumers and users. Although it is an issue associated more with energy distribution. However, the entire energy system from generation to transmission and distribution requires effective monitoring both for transparency and reliability. The level of attention that has concentrated on remote energy consumption and monitoring at all levels cannot be ignored especially in the days of modern technology applications and soft solutions. This survey tends to examine the level of implementation and associated challenges in remote energy consumption and monitoring. A comprehensive appraisal of previous proposals and formulated frameworks from different perspectives were considered as a basis for this research work. This work presented a review of modern models and approaches in energy monitoring especially, carrying out this activity remotely i.e., away from the physical location of where energy is being consumed or utilized. Trends of energy monitoring and consumption at different levels ranges from power generation, transmission and distribution including Supervisory Control and Data Acquisition (SCADA) systems were discussed in line with their difficulties. The outcome of the review was discussed and this work provided areas where future technologies and models could be developed to enhance remote energy consumption monitoring with the use of modern technologies.